The endocannabinoidome mediator N-oleoylglycine is a novel protective agent against 1-methyl-4-phenyl-pyridinium-induced neurotoxicity - Lauritano, Anna; Cipollone, Irene; Verde, Roberta; Kalkan, Hilal; Moriello, Claudia; Iannotti, Fabio Arturo; Di Marzo, Vincenzo; Piscitelli, Fabiana (Frontiers in Aging Neuroscience, 2022)
N-oleoylglycine (OlGly) is a lipid mediator that belongs to the expanded version of the endocannabinoid (eCB) system, the endocannabinoidome (eCBome) and has recently gained increasing attention from the scientific community for its protective effects in a mouse model of mild traumatic brain injury. However, the effects of OlGly on cellular models of Parkinson's disease (PD) have not yet been investigated, whilst other lipoaminoacids have been reported to have beneficial effects. Moreover, the protective effects of OlGly seem to be mediated by a direct activation of proliferator-activated receptor alpha (PPARα), which has already been investigated as a therapeutic target for PD. Therefore, this study aims to investigate the possible protective effects of OlGly in an in vitro model obtained by treating the neuroblastoma cell line, SH-SY5Y (both differentiated and not) with 1-methyl-4-phenyl-pyridinium (MPP+), which mimics some cellular aspects of a PD-like phenotype, in the presence or absence of the PPARα antagonist, GW6471. Our data show that MPP+ increases mRNA levels of PPARα in both not differentiated and differentiated cells. Using assays to assess cell metabolic activity, cell proliferation and pro-inflammatory markers, we observed that OlGly (1 nM), both as treatment (1h) and pre-treatment (4h), is able to protect neuronal damage induced by 24 h MPP+ exposure through PPARα. Moreover, using a targeted lipidomics approach, we demonstrate that OlGly exerts its effects also through the modulation of the eCBome. Finally, treatment with OlGly was able also to reduce increased IL-1induced by MPP+ in differentiated cells. In conclusion, our results suggest that OlGly could be a promising therapeutic agent for the treatment of MPP+-induced neurotoxicity.